HORROR AND THE BODY: UNDERSTANDING THE REWORKING OF THE GENRE IN MARINA DE VAN’S DANS MA PEAU/IN MY SKIN (2001) - Chareyron, Romain (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
This article explores how Marina de Van’s confrontational representation of the human body, in her film Dans ma peau/In my Skin (2001), should be understood as a reinterpretation of certain major themes in the horror genre. More specifically, I examine how de Van’s mise-en-scène borrows from the genre of horror , both on a visual and a technical level, to deconstruct the meanings initially attached to the representation of the body in pain found in horror’s narratives. I argue that a close analysis of the textural properties of the image allows for a reappraisal of the onscreen presence of the wounded body, this body departing from horror’s straightforward visual regimen, to open up a space for the character’s subjectivity to emerge. I also posit that the use of the close-up on images of blood and scars, while being reminiscent of horror’s treatment of the body, becomes a vehicle for the unleashing of the character’s unmediated drives to explore her own flesh and to reach a new level of self-awareness.